The Role of Directed Dispersal in Driving Genetic and Morphological Structure in Invasive Smallmouth Bass - Diedericks, Genevieve; Broeckhoven, Chris; von der Heyden, Sophie; Weyl, Olaf L. F.; Hui, Cang (Frontiers in Ecology and Evolution, 2022)
Dispersal is an essential life-history trait crucial to species persistence and diversification. This is particularly important in spatiotemporal fluctuating environments such as freshwater habitats, where species movement is confined to the dendritic network and wetted boundaries. To persist in such fluctuating environments, a species can modify, adaptively and plastically, its phenotypic variation to better match the environment or escape via directed dispersal to a more suitable habitat (i.e., matching habitat choice). We use the invasive smallmouth bass, Micropterus dolomieu, sampled at 10 km intervals, to assess the effect of directed dispersal on the fine scale genetic and phenotypic variation in populations of M. dolomieu along a river course. Gene flow was used as a proxy for dispersal. By comparing population genetic structure, morphological variation (of linear traits and geometric landmarks), and environmental heterogeneity, we discovered a clear correlation between environmental variation and morphological traits. Although isolation by distance seemed to have shaped the overall genetic pattern detected among the populations, the strong genetic structuring observed within the Ratel tributary appeared to be non-random. These results provide novel insights into the potential mechanisms promoting the spread and establishment of invasive species and the possible influence multiple introductions may have on fine scale genetic structuring.